2016
DOI: 10.1148/radiol.2016151789
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Retear after Repair of Full-Thickness Rotator Cuff Tear: Two-Point Dixon MR Imaging Quantification of Fatty Muscle Degeneration—Initial Experience with 1-year Follow-up

Abstract: Purpose To determine the degree of preoperative fatty degeneration within muscles, postoperative longitudinal changes in fatty degeneration, and differences in fatty degeneration between patients with full-thickness supraspinatus tears who do and those who do not experience a retear after surgery. Materials and Methods This prospective study had institutional review board approval and was conducted in accordance with the Committee for Human Research. Informed consent was obtained. Fifty patients with full-thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 35 publications
2
54
0
Order By: Relevance
“…One recent report also utilized quantitative fat imaging to evaluate progression of fatty infiltration after rotator cuff repair. 13 Nozaki et al 13 showed that patients with an eventual repair failure had higher baseline fat measurements in the supraspinatus. We observed a higher mean fat fraction at preoperative imaging for patients with an eventual repair failure compared with those with an intact repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One recent report also utilized quantitative fat imaging to evaluate progression of fatty infiltration after rotator cuff repair. 13 Nozaki et al 13 showed that patients with an eventual repair failure had higher baseline fat measurements in the supraspinatus. We observed a higher mean fat fraction at preoperative imaging for patients with an eventual repair failure compared with those with an intact repair.…”
Section: Discussionmentioning
confidence: 99%
“…16 Recently, there has been increased interest in the quantitative assessment of fatty infiltration with chemical shift–based MRI. 8,12,13 One method, the iterative decomposition of echoes of asymmetric length (IDEAL), has been shown to be both reproducible and to correlate with the Goutallier classification. 12 By using this sequence, precise fat fraction measurements that represent the percentage of intramuscular fat can be determined within any defined region of interest.…”
mentioning
confidence: 99%
“…17,28,33 2-point VIBE Dixon was selected because of its wide availability and well documented recent use in the muscle. 26,29,[33][34][35][36][37][38] Diffusion-weighted images (DWI) were acquired using a STEAM prototype sequence with an echoplanar imaging (EPI) readout 39 with spectral adiabatic inversion recovery fat suppression: TR/ TE: 6300 ms/42. 4…”
Section: Mr Measurementsmentioning
confidence: 99%
“…Researchers have recently reported various ways of assessing rotator cuff tendon tears preoperatively. Nozaki et al [17] applied 2-point Dixon MRI to rotator cuff muscles and suggested that the fat fraction observed preoperatively may offer a way to predict the recurrence of a tear after repair surgery. Rosskopf et al [18] proposed that a preoperative evaluation of the supraspinatus muscle can help to establish a treatment plan, while measuring shear wave velocity by SWE can help to assess mechanical muscle properties and to determine the prognosis of a torn rotator cuff tendon.…”
Section: Discussionmentioning
confidence: 99%